Kinetics of anaerobic biodegradation of slurry of compost in liquid waste of tofu on batch process - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2001)
This research was to study the effects of reaction temperature and reactant ratio on the production rate of biogas and the kinetics of cell growth and substrate consumption. This study was carried out on laboratory scale, batch reactor, ,anaerobic process, and cow dung as starter. The temperature effects was studied in mesophilic phase between 30 Â°C to 45 Â°C and the reactant ratio was between 0.4 to 0.4556 g compost per mL liquid waste of tofu industry. The result of the experiment showed that the maximum production rate of biogas was reached when the reaction temperature 40 Â°C and the reacrant ratio 0.4444 g compost per mL liquid waste of tofu industry. Also, for this condition the maximum specific growth rate of the cell was 0.0044 hour'. The effects of the reaction temperature on the maximum specific growth rate fitted the equation of pâ,2/pâ,1 = 1.0789(r2-n) and the average relative errors 1.61%.